Advancements in microenvironment-based therapies: transforming the landscape of multiple myeloma treatment - Lu, Ke; Wang, Wen; Liu, Yuntong; Xie, Chao; Liu, Jiye; Xing, Lijie (Frontiers in Oncology, 2024)
Multiple myeloma (MM) is the most prevalent malignant monoclonal disease of plasma cells. There is mounting evidence that interactions with the bone marrow (BM) niche are essential for the differentiation, proliferation, survival, migration, and treatment resistance of myeloma cells. For this reason, gaining a deeper comprehension of how BM microenvironment compartments interact with myeloma cells may inspire new therapeutic ideas that enhance patient outcomes. This review will concentrate on the most recent findings regarding the mechanisms of interaction between microenvironment and MM and highlight research on treatment targeting the BM niche.